Problemy strategicznego zarządzania elastycznością systemów informacyjnych - Skwarnik, Marek (Problems of MIS flexibility strategic management, 2006)
The turbulent enterprise environment enforces adequate MIS changes. Without these modifications efficiency of management processes and procedures may dramatically decrease. First we propose MIS flexibility management as advanced, organized form of information system changes preparation. We focus on strategic phase of these preparation. We propose MIS flexibility strategy typology. First of all we describe active, passive and mixed forms of flexibility strategy. Then we analyse feasibility of these strategies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 47-55